Ecological risk assessment of heavy metals in brown trout (Salmo trutta m. fario) from the military training area Boletice (Czech republic) - Dvořák, Petr; Andreji, Jaroslav; Mráz, Jan; Dvořáková Líšková, Zuzana; Klufová, Renata (Maghira and Maaspublications, 2016)
This study to assess the environmental pollution status in streams (Loutecky, Spicak, Olsina, Trebovicky, Polecnicky and Luzny) from the Boletice area. Were determined of some metal (Hg, Pb, Cd) concentrations in the muscle and correlations among selected metals as well as standard length and total weight in brown trouth – Salmo trutta morpha fario. The contents of the analyzed metals in muscles were Hg 0.19–0.72, Pb 0.01–0.6 and Cd 0.020–0.083 mg.kg–1 wet weight basis and these concentrations did not exceed the limits admissible in the Czech Republic. The Czech republic permissible limit for Hg (0.5 mg/kg to omnivors, 1 mg/kg to predators), Pb (0.3 mg/kg) and Cd (0.05 mg/kg) defined in the Codex Alimentarius for safe human consumption exceeded in 6%, 3%, and 0% of analyzed samples for Hg, Pb and Cd respectively. On an average, the order of metal concentrations in the fish muscle was: Hg>Pb>Cd.
Keywords: toxic metal; fish, ecological risk; military training area Boletice